Effect of pretreatment on the shelling strength of cashew nut shell - Kumar, Ashok; Borah, Swapnali (Journal of Postharvest Technology, 2023)
India is the second largest producer of cashew nut in the world. Raw cashew nuts are pre-conditioned either by roasting or steaming before shelling. The specific objective of this study was to evaluate the effect of pretreatment (roasting and steaming) on the shelling strength of cashew nut shell and its effect on whole kernel out turn. The texture analyzer (Model TA-XT plus) with the probe, HDP/BSK blade set with knife, and heavy duty platform was used for the determination of the strength of cashew nut shell and cashew nut kernel. Strength of raw cashew nut shell decreased from 39.2 ± 2.8 kg to 18.6 ± 4.8 kg for roasting and 29.2 ± 10.5 kg for steaming. Manual shelling of roasted cashew nut shell was easy compare with that of steamed cashew nut shell. The WKO was about 98.9±2.65% for roasting and 97.11±1.25% for steaming, whereas it was about 38±3 % for raw cashew nut shell. Pretreatment influenced and decreased the strength of raw cashew nut shell significantly and further improved in WKO and shelling efficiency.